A Socio-Linguistic Inquiry Into Language Change: Alsatian, A Case Study - Hessini, Marguerite (Kansas Working Papers in Linguistics, 1979)
Alternating French and German dominance, and concomitant differing language policies, have determined the sociolinguistic position of Alsatian, a German dialect, spoken in Eastern France. Subjected to policies aimed at producing linguistic assimilation and uniformity, Alsatian has survived as an unwritten speech and has become a symbol of ethnic identity. Through intensive and prolonged exposure to French, it has incorporated numerous French borrowings which underwent various characteristic phonological and morphological changes. More recently, a general trend toward regionalism in France and an upsurge of protest movements, aiming at defending the rights of minorities, have generated a revival of the dialect.